Development and applications of intensity modulation based fiber optic displacement sensors / Yang Hangzhou - Yang, Hangzhou (2012)

(untitled)
This thesis presents various designs and applications of fiber optic displacement sensors (FODSs) which are based on intensity modulation technique in conjunction with multimode plastic optical fiber. Various FODS designs have been proposed using different sensor probes and reflective targets. In the design of sensor probes, the linear range of FODS with two receiving fibers bundles parallel is increase almost double comparison with that of conventional FODS. In the concentric format of sensor probe, from the results of experimental a higher number of receiving fiber surrounded the higher sensitivity of FODS is achieved and a theoretical model of 16 receiving fiber surrounding the transmitting fiber is setup. In the sensor probe formed with asymmetrical fiber bundled parallel, the sensor performance is investigated by variants Core Radius Ratios, the smaller CRR can achieves higher sensitivity and the bigger CRR is produced longer displacement measurement range. In the asymmetrical fiber inclined with angle, both the results of theoretical and experimental are shown that the bigger inclination angle combines with small CRR are generated higher sensitivity. Also, the sensor performance is studied by different contributing factor, such as, laser sources and target reflectors. In the FODS with concave mirror as a target, both theoretical and experimental results show that the displacement response is governed by focal length and diameter of concave mirror. The longest displacement range 26mm is obtained by using a concave mirror focus length of 12mm. A three axes displacement sensing is proposed, the maximum measurement range of about 20 mm is obtained using a focal length of 10 mm. In the y and z-axis displacement measurements, the longest linear range of 8 mm is achieved at mirror radius of 10 mm. The FODS are then used for various applications such as estimation of surface roughness, sensing of liquid refractive index and glucose concentrations, monitoring of liquid level, as well as vibration measurement.